Leveraging deep learning algorithms for the timely detection of diseases in bean leaves - Fiona, Driciru; Denish, Ajani (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2024.